2001
DOI: 10.1073/pnas.171023398
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular distribution of epothilones in human tumor cells

Abstract: Epothilones are a new class of natural and potent antineoplastic agents that stabilize microtubules. Although 12,13-epoxide derivatives are potent antiproliferative agents, the activities of the corresponding 12,13-olefin analogs are significantly decreased. These data were confirmed for two new analogs, 6-propyl-EpoB (pEB) and 6-propyl-EpoD (pED), in comparison with the natural compounds EpoB͞EpoD, by using human A431, MCF7, and MDR1-overexpressing NCI͞Adr cells. By using tritiated pEB͞pED, compound uptake, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 32 publications
(40 reference statements)
5
32
0
Order By: Relevance
“…First, γH2AX foci assays showed that ionizing radiation combined with epothilone B resulted in a concentration-dependent increase of the number of double-strand breaks which suggests a reduction in DNA repair capacity. Lichtner et al [27] published their observation of a strong accumulation of epothilone B in the cell nucleus, more precisely in the fraction of nuclear proteins. This indicates an inhibition of proteins like the nuclear tubulin isotype [27] which, thus, results in a possible DNA-damaging effect of epothilone B [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, γH2AX foci assays showed that ionizing radiation combined with epothilone B resulted in a concentration-dependent increase of the number of double-strand breaks which suggests a reduction in DNA repair capacity. Lichtner et al [27] published their observation of a strong accumulation of epothilone B in the cell nucleus, more precisely in the fraction of nuclear proteins. This indicates an inhibition of proteins like the nuclear tubulin isotype [27] which, thus, results in a possible DNA-damaging effect of epothilone B [9].…”
Section: Discussionmentioning
confidence: 99%
“…Lichtner et al [27] published their observation of a strong accumulation of epothilone B in the cell nucleus, more precisely in the fraction of nuclear proteins. This indicates an inhibition of proteins like the nuclear tubulin isotype [27] which, thus, results in a possible DNA-damaging effect of epothilone B [9]. Swanton et al [41] emphasized that the effect of microtubulestabilizing agents is based on the repression of genes which play a role in DNA repair (e.g., BRCA1, H2AFX).…”
Section: Discussionmentioning
confidence: 99%
“…The pan caspase inhibitor benzyloxycarbonylVal-Ala-Asp(OMe).fluoromethylketone (Z-VAD-fmk) was purchased from Bachem AG. Stock solutions were prepared and stored as previously detailed (18).…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that some epothilones may overcome multidrug resistance (MDR) mechanisms, which would augment their therapeutic potential. Natural epothilones, however, are not optimal candidates for anticancer therapy for a number of reasons, including a limited therapeutic index and poor tolerability (18)(19)(20). Because of this, novel epothilone derivatives have been synthesized and investigated in preclinical models (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] In contrast to paclitaxel, epothilones in general are equally cytotoxic against paclitaxelsensitive and paclitaxel-resistant human cancer cell lines, including those overexpressing MDR1/Pgp. 11,[13][14][15][16]28,29 In addition, although point mutations in the major expressed ␤-tubulin isoform result in a 24-fold increase in resistance to paclitaxel, these same mutations result in only a 1.3-to 4-fold cross-resistance to patupilone. 28 To date, patupilone has been evaluated in 2 phase 1 studies, and several phase 2 clinical trials are ongoing.…”
Section: Introductionmentioning
confidence: 99%